(3JMaI GdeLGgOjf aj GdYed HGdejGOjfs - (3GdnqQnqeGM; eMeO Hf dGLjf Hf YHO Gddg GdMSGej,J (B780 (3g` s
(3ChdgG (B:s
(3hHYO aEf ddMQhH dhGRe dGHO ddeJUa HGdTLGYI efgG s
(3BNQgG (B:s
(3Je GdcJGH ZaQ Gddg JYGdi deGdcg hcGJHI hbGQFg heSJeYg hdWa Hge CLeYjf HGddWa GdNai Bejf s
(3Hg CTcGd ejGOjf GdMQHs
(3fSNI ecQQI JMJ Qbe (B11 (3afhf MQHjI haQhSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B15 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B164s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B373s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs